The Benefits of Cloud on University System - Hachem Alaoui Harouni, Moulay; Hachem, El-Kaber; Ziti, Cherif (International Journal of Engineering and Technology, 2018)
With the growth of the number of students and their data, the cloud will help university to deal with different challenges about security, privacy and compliance, and to get some advantages of infrastructure to the cloud such as universal access, low entry cost, elasticity, scalability, and so on. This paper is going to illustrate an operation that allows university to migrate its system to the cloud with the purpose of meeting its requirements.Â Â